2019
DOI: 10.1111/aej.12379
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of a guided endodontics protocol for removal of fibre‐reinforced posts

Abstract: This paper demonstrates the usefulness of endodontic guides for the removal of fibre posts. A 36-year-old man consulted for retreatment of a maxillary first molar presenting a periapical pathology. This tooth revealed a composite reconstruction together with a glass-fibre post in the palatal root canal. To assist removal, use of an endodontic 3D-printed guide was indicated. A cone beam computed tomography examination and an optical impression were made to produce a tooth-supported guide by means of implant pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
1
29
0
4
Order By: Relevance
“…From the 37 selected case reports ( Table 2 ), 25 of them had at least one year of follow-up with excellent results in terms of the absence of symptomatology or evidence of bone regeneration [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Eighteen of them were performed with only single-rooted teeth [ 3 , 9 , 38 , 40 , 44 , 46 , 50 , 51 , 52 , 53 , 55 , 58 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the 37 selected case reports ( Table 2 ), 25 of them had at least one year of follow-up with excellent results in terms of the absence of symptomatology or evidence of bone regeneration [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Eighteen of them were performed with only single-rooted teeth [ 3 , 9 , 38 , 40 , 44 , 46 , 50 , 51 , 52 , 53 , 55 , 58 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that drilling precision decreased when a drill with a small diameter was used and selection of guide drill diameter should correlate with post diameter [ 12 13 14 ]. In contrast, a drill with a large diameter could cause more heat generation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many authors have used computer-aided static navigation procedures to perform the endodontic access cavity in calcific metamorphosis cases [26][27][28] or dental malformations as dens invaginatus [29,30] or dens evaginatus [31]. Furthermore, computer-aided static navigation techniques have also been used to remove prosthetic fiber post into the root canal system [32,33] and guide prosthetic dental crown preparations [34]. The accuracy of endodontic procedures performed by computer-aided static navigation techniques has led to the application of the computer-aided static navigation technique to endodontic surgery procedures.…”
Section: Discussionmentioning
confidence: 99%